2021
DOI: 10.3390/plants10040717
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach for Species Identification and Quality Analysis for Labisia pumila Using DNA Barcoding and HPLC

Abstract: Labisia pumila is a precious herb in Southeast Asia that is traditionally used as a health supplement and has been extensively commercialized due to its claimed therapeutic properties in boosting a healthy female reproductive system. Indigenous people used these plants by boiling the leaves; however, in recent years it has been marketed as powdered or capsuled products. Accordingly, accuracy in determination of the authenticity of these modern herbal products has faced great challenges. Lack of authenticity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The strength of these sequences and their containment of many areas of difference appeared here, as the A. species closest to A. saudiarabica here had some more diversity than its predecessor in the case of matK gene. Also, the results showed that the pairs of primers ITS1 were not sufficiently specific like ITS2, which often in the first attempts do not give good results, while the trend here is the latest and closest to use and distinguish plant species is through the regions of ITS2 (26,27). In conclusion, it can be said that among the genetic markers on which the study was conducted, the efficiency of the matK and ITS2 sequences appeared to distinguish A. saudiarabica plant, and therefore the study recommends using them to document this rare plant.…”
Section: Discussionmentioning
confidence: 82%
“…The strength of these sequences and their containment of many areas of difference appeared here, as the A. species closest to A. saudiarabica here had some more diversity than its predecessor in the case of matK gene. Also, the results showed that the pairs of primers ITS1 were not sufficiently specific like ITS2, which often in the first attempts do not give good results, while the trend here is the latest and closest to use and distinguish plant species is through the regions of ITS2 (26,27). In conclusion, it can be said that among the genetic markers on which the study was conducted, the efficiency of the matK and ITS2 sequences appeared to distinguish A. saudiarabica plant, and therefore the study recommends using them to document this rare plant.…”
Section: Discussionmentioning
confidence: 82%
“…This has become a source of concern for botanical drugs suppliers, as wild M. pumilum is known to grow slowly in its natural habitat. As a result, several research institutions have conducted extensive tissue culture breeding for M. pumilum to keep up with the expanding market demand ( Tarmizi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Fagaceae) had no DNA sequence. Additionally, a recent study by Tarmizi et al (2021) effectively used DNA barcoding and HPLC techniques for the identification of cultivated M. pumilum var. alata and var.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic authentication-based chromatographic profiling method is an emerging technique that is mainly performed by DNA-barcoding hyphenated chromatographic analysis. The combined method provides species-level accuracy of herbal samples, and therefore, a more reliable classification of those samples can be acquired by chemical analysis [ 19 ]. This technique has been applied to the chemical classification of diverse herbal medicines, such as Arnebia [ 20 ], Fritillaria [ 21 ], Phellodendron [ 22 ], and Daphne [ 23 ] species.…”
Section: Introductionmentioning
confidence: 99%